PEMBAHARUAN KETENTUAN PENGAMPUAN DALAM KUHPERDATA DALAM MEWUJUDKAN PELINDUNGAN HUKUM - Ritonga, Francois Geny; Sitohang, Mawar (Fakultas Hukum Universitas Kristen Indonesia, 2024)
Civil law regulates the substance of the rights (recht) and obligations (verplicht) of legal subjects. According to Soebekti, civil law is all the basic laws that regulate individual interests. One of these interest arrangements is regulated in the provisions of Article 433 of the Civil Code (Civil Code). If the interests are met by the conditions as regulated in these provisions, the entitled parties can submit a request for a Determination of Custody through the District Court. However, with the times and progressive legal developments, there are individual interests that need to receive legal protection, including people with mental disabilities and/or intellectual disabilities. The Constitutional Court has decided to grant partial material review of Article 433 of the Civil Code against the 1945 Constitution through Decision Number 93/PUU-XX/2022, where this decision can demonstrate the renewal of the guardianship provisions in the Civil Code in realizing legal protection.